A History of Contested Narratives: The National Film Board of Canada’s Evolving Cinematic Treatment (1945–2018) of the Internment of Japanese Canadians during World War Two - George Melnyk (Anglica. An International Journal of English Studies, 2021)
The National Film Board of Canada (NFB) is world-renown for its documen- taries and animations. This article examines how the NFB dealt with one specific topic – the internment of Japanese Canadians during World War Two. By analyzing the films produced by the NFB between 1945 and 2018, this study seeks to understand how and why its narratives of the internment changed dramatically over three-quarters of a century. The study deals with six NFB films: Of Japanese Descent (1945), Enemy Alien (1975), Minoru: Memory of Exile (1992), Freedom Has a Price (1994), Sleeping Tigers: The Asahi Baseball Story (2003), and East of the Rockies (2018). Drawing on the postcolonial concepts of the colonizing gaze and hegemony, as well as poststructuralist concepts of the trace and discourses of power, it probes the evolution of the NFB’s cinematic culture and concludes that the NFB’s film legacy parallels a changing public discourse in Canada on this traumatic historical violation of human rights.